Collaborating remotely: an evaluation of immersive capabilities on spatial experiences and team membership. Issue 4 (3rd April 2018) - Oprean, Danielle; Simpson, Mark; Klippel, Alexander
ABSTRACT: Today's workforce environments are steadily becoming more distributed across the globe, calling for improved ways of facilitating collaborations at a distance, including geo-collaborations or collaborations at critical locations. Newer technology is allowing distributed teams to move away from traditional conference rooms, taking collaborations into the field and giving remote teams more information about the environment. This idea of situating a remote collaborator's experiences in the field, virtually, promises to enhance the understanding of geographically remote spaces. Newer technologies in virtual reality (VR) hold promise for providing mobile spatial experiences in real-time, without being tied to fixed hardware, such as systems in conference rooms. An exploratory study using VR technology on remote user experiences in a collaboration was conducted to identify the added value for remote collaborators. The findings suggest immersive capabilities improve feelings of presence in the remote locations and perceptions of being in the remote location increase feelings of team membership.